Utilization of Artificial Dura for Anterior Skull Base Reconstruction Following Transcranial Resection of Benign Cranionasal Communicating Tumors: Technical Note - He, Junhua; Wang, Bo; Wang, Xingchao; Li, Peng; Liuge, Mingtian; Bie, Zhixu; Yin, Jie; Bi, Zhiyong; Liu, Pinan (Journal of Neurological Surgery Part B: Skull Base, 2025)
Objective The purpose of this study was to introduce a watertight duraplasty with artificial dural grafts for anterior skull base (ASB) reconstruction.Methods Between November 2019 and October 2023, we used artificial dural grafts for the ASB reconstruction in 10 cases of recurrent benign cranionasal communicating tumors. Through a transcranial subfrontal approach, the tumor was totally removed and the skull base defect was repaired using the NormalGEN® and DuraMax® artificial dural grafts. Clinical and imaging follow-ups were conducted to screen for the occurrence of postoperative cerebrospinal fluid (CSF) leakage, intracranial infection, and encephalocele.Results Gross total resection of tumor and ASB reconstruction with the artificial dural grafts were achieved in 10 patients. The patients were followed up clinically for 11 to 52 months (mean 26.0 months) and underwent medical imaging follow-up for 6 to 36 months (mean 18.4 months). One patient presented with CSF leakage on day 47 after the operation. Another patient endured intracranial infection without CSF leakage on the fifth day after the operation. Both patients were cured. No encephalocele was observed during the follow-up period. All the patients achieved a favorable recovery.Conclusion Following transcranial resection of benign cranionasal communicating tumors, we utilized artificial dural grafts for ASB reconstruction when the frontal pericranium was impaired by tumor invasion or previous surgery. Our initial experience and postoperative follow-up have proven that the method is feasible and reliable in selected cases.
Keywords: anterior skull base; cranionasal communicating tumor; reconstruction; artificial dural graft